The influence of HIV infection on myocardial fibrosis diagnosed by cardiac magnetic resonance imaging in adults: a systematic review and meta-analysis of observation studies - Mutengo, Katongo Hope; Lima, Bruno Bezerra; Mutale, Wilbroad; Mweemba, Aggrey; Kabwe, Lorrita; Banda, Clive; Kaayunga, Callistus; Mulenga, Mutale; Heimburger, Douglas; Masenga, Sepiso K.; Carr, John Jeffrey; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHuman immunodeficiency virus (HIV) infection is linked to myocardial fibrosis. Observational studies using cardiac magnetic resonance (CMR) have explored this relationship but scarcity of data synthesis limits our understanding. Our systematic review and meta-analysis aimed to synthesize associations between HIV and myocardial fibrosis from CMR-based observational studies in adults.MethodsWe identified 12 studies (2013–2024) with 1,769 participants [1,117 people with HIV (PWH)]. Three studies were cohort and nine were cross-sectional. Meta-analysis included seven studies on late gadolinium enhancement (LGE) (1,081 participants: 669 PWH), eight on native T1 mapping (840 participants: 467 PWH), and ten on ECVF (1,603 participants: 992 PWH). We examined myocardial fibrosis prevalence via the prevalence difference in LGE, and severity by mean differences in native T1 mapping values [milliseconds (ms)] and global extracellular volume fraction (ECVF,%) between PWH and HIV-uninfected individuals, using random effects model.Results and discussionPooled analyses showed PWH had a 33% higher prevalence of LGE (95% CI: 12.0%–54.0%, I2 = 94.5%, p < 0.001), a mean native T1 mapping difference of 27.30 ms (95% CI: 11.21–43.39 ms, I2 = 88.2%, p < 0.001), and a mean ECVF difference of 1.85% (95% CI: 0.63%–3.08%, I2 = 90.5%, p < 0.001), respectively. Meta-regression showed no significant associations between ECVF and demographic, HIV-related, or cardiac factors. LGE and native T1 mapping analyses lacked sufficient data for meta-regression. In conclusion, PWH exhibit significantly higher prevalence and severity of myocardial fibrosis compared to HIV-uninfected individuals. But standardized methodologies and further research are essential to enhance consistency.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=533379, CRD [42024533379].